The role of radiotherapy in HER2+ early-stage breast cancer patients after breast-conserving surgery - Yang, Huanzuo; Qiu, Mengxue; Feng, Yu; Wen, Nan; Zhou, Jiao; Qin, Xiangquan; Li, Juan; Liu, Xinran; Wang, Xiaodong; Du, Zhenggui (Frontiers in Oncology, 2023)
Background: Some HER2+ patients may gain limited benefit from radiotherapy (RT) after breast-conserving surgery (BCS) due to radio-resistance. This study aimed to develop an individualized nomogram to identify early-stage HER2+ patients who could omit RT after BCS. Methods: The data of HER2+ patients with T0-2N0M0 breast cancer after BCS between 2010 and 2015 were extracted from Surveillance, Epidemiology, and End Results (SEER). Based on the independent prognostic factors determined by the Cox analysis in patients without RT after propensity score matching (PSM), the nomogram and risk stratification model were constructed, and then the prognosis of patients with and without RT was compared in each stratified group. Results: A total of 10799 early-stage HER2+ patients after BCS were included. Baseline characteristics were similar between groups after PSM. Multivariate Cox analysis indicated that RT could improve overall survival (OS) (HR: 0.45, P<0.001) and breast cancer-specific survival (BCSS) (HR: 0.53, P<0.001). Age, marital status, tumor location, tumor size and chemotherapy were identified by multivariate Cox analysis in patients without RT and were incorporated into a well-validated nomogram. The risk stratification model based on the nomogram indicated that RT was associated with improved OS (HR 0.40, P< 0.001) and BCSS (HR 0.39, P< 0.001) in the high-risk group but not in the low-risk group [OS: HR 1.04, P = 0.94; BCSS: HR 1.06, P = 0.93]. Conclusion:RT could significantly improve the OS and BCSS of HER2+ early-stage breast cancer patients after BCS on the whole. For high-risk patients, RT is an essential component of cancer therapy. However, the omission of radiotherapy may be considered for low-risk HER2+ early-stage patients. Further validation and improvement of the nomogram by prospective study or randomized controlled trials are warranted.